Comparison of the companies on the BIST sustainability index with other listed companies in the context of earnings manipulation - ATİK YILDIRIM, ASUMAN (My University, 2022)
The concept of sustainability has been gaining importance all over the world. Concerns of consumers, investors, fund providers and governmental organizations about sustainability motivate companies to take action for a more sustainable world. Stock exchanges have also created sustainability related indices. The starting point of this study is the assumption that companies in the sustainability index are more respectful to the environment, society and economy and therefore, they are also more trustworthy when presenting their earnings. Earnings manipulation was detected by using the Beneish Model (1999). The M-scores of BIST non-financial firms were calculated for the years 2017 (262 firms) and 2018 (261 firms). The results showed that nearly half of the sample firms were possibly manipulators in both years. Additionally, nearly 40 percent of the firms on the sustainability index were manipulators. Although the percentage of manipulating firms in the sustainability index is lower compared to the percentage of manipulators in all firms, according to the results of statistical tests, there is no significant difference between the earnings manipulation behaviours of companies in the sustainability index and those not in the index.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Çalışma Ekonomisi; Social Sciences and Humanities; Labor Economics and Industrial Relations; Labor Economics; İŞ FİNANSI; Ekonomi ve İş; Sosyal Bilimler (SOC); BUSINESS, FINANCE; ECONOMICS & BUSINESS; Social Sciences (SOC); Finans; Muhasebe; İşletme, Yönetim ve Muhasebe (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Finance; Accounting; Business, Management and Accounting (miscellaneous); Social Sciences & Humanities; Sustainability; Sustainability index; BIST; Earnings manipulation; Beneish model; CORPORATE SOCIAL-RESPONSIBILITY; FINANCIAL PERFORMANCE; FIRMS; MANAGEMENT; Sustainability; Sustainability index; BIST; Earnings manipulation; Beneish mode